Impact of Combinations of Donor and Recipient Ages and Other Factors on Kidney Graft Outcomes - Gerbase-DeLima, Maria; de Marco, Renato; Monteiro, Franscisco; Tedesco-Silva, Hélio; Medina-Pestana, José O.; Mine, Karina L. (Frontiers in Immunology, 2020)
As the availability of kidneys for transplantation continues to be outpaced by its growing demand, there has been an increasing utilization of older deceased donors in the last decades. Considering that definition of factors that influence deceased donor kidney transplant outcomes is important for allocation policies, as well as for individualization of post-transplant care, the purpose of this study was determine the risks for death censored graft survival and for patient survival conferred by older age of the donor in the context of the age of the recipient and of risk factors for graft and/or patient survival. The investigation was conducted in a single-center cohort of 5,359 consecutive first kidney transplants with adult deceased donors performed on non-prioritized adult recipients from January 1, 2002, to December 31, 2017. Death censored graft survival and patient survival were lower in older donors, whereas graft survival was higher and patient survival was lower in old recipients. The analyses of combinations of donor and recipient ages showed that death censored graft survival was lower in younger recipients in transplants from 18 to 59-year old donors, with standard or extended criteria, but no difference in graft survival was observed between younger and older recipients when the donor was ≥ 60-year old. Patient survival was higher in younger recipients in transplants with younger or older donors. Two to six HLA-A,B,DR mismatches, when compared to 0-1 MM, conferred risk for death-censored graft survival only in transplants from younger donors to younger recipients. Pre-transplant diabetes conferred risk for patient survival only in 50-59-year old recipients, irrespectively of the age of the donor. Time on dialysis ≥ 10 years was a risk factor for patient survival in transplants with all donor-recipient age combinations, except in recipients with ≥ 60 years that received a kidney from an 18-49-year old donor. In conclusion, the results obtained in this study underline the importance of analyzing the impact of the age of the donor taking into consideration different scenarios.